KISAH SEORANG PRAMURIA: MAKNA TUBUH, INTIMASI, DAN SEKSUALITAS PADA PEREMPUAN LADY COMPANION DI SURAKARTA - Silvani Adiningtyas; Rezza Dian Akbar (UNIVERSITAS SEBELAS MARET (UNS), 2023)
This study aims to explore the social phenomena that occur in the nightlife, namely the Lady Companion phenomenon or commonly called karaoke guides which are closely related to the practice of prostitution. And what is the meaning of sexual relations and intimacy by LC women who are prostitutes and what is the meaning of the body and